The Effect of Junior Auditors’ Trust in Superiors and Communication Modes on Auditors’ Voice Decisions - Li, Ran; Giambatista, Robert C.; Boyle, Douglas M. (Journal of Knowledge Management Practice, 2025)
This study examines how staff auditors’ trust in superiors and communication modes affect their voice decisions in distributed audit teams. In a 3×2 experiment involving 150 junior auditors from the U.S. and China, trust (higher-level vs. lower-level) and communication modes (face-to-face, traditional remote communication, and live video conference) were manipulated. Results show that greater trust in superiors increases auditors’ willingness to speak up. Furthermore, junior auditors exhibit greater willingness to communicate upward in face-to-face condition than in traditional remote communication. While live video conferencing results in the lowest voice. Findings offer practical insights in remote and global audit environments.